2012
DOI: 10.1007/s10460-012-9381-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the good farmer identity: shifts in farmer identities and farm management practices to improve water quality

Abstract: All farmers have their own version of what it means to be a good farmer. For many US farmers a large portion of their identity is defined by the high input, high output production systems they manage to produce food, fiber or fuel. However, the unintended consequences of highly productivist systems are often increased soil erosion and the pollution of ground and surface water. A large number of farmers have conservationist identities within their good farmer identity, however their conservation goals often nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(172 citation statements)
references
References 47 publications
4
166
0
2
Order By: Relevance
“…Priorities are multiple and heterogeneous across the farming community (Atwell et al, 2009a(Atwell et al, , 2009b, and policies are needed that allow for flexibility under changing socioeconomic and physical conditions. Programs that bring farmers together and generate a collective sense of what is needed for improving conservation may also be helpful (McGuire et al, 2013). Without creating new efficiency-based subsidy programs, we will need every farm and every farmer in Illinois actively implementing some form of end-of-pipe remediation practice to address this issue on such a scale.…”
Section: Biophysical and Social Science Results Inform Policy Decisionsmentioning
confidence: 99%
“…Priorities are multiple and heterogeneous across the farming community (Atwell et al, 2009a(Atwell et al, , 2009b, and policies are needed that allow for flexibility under changing socioeconomic and physical conditions. Programs that bring farmers together and generate a collective sense of what is needed for improving conservation may also be helpful (McGuire et al, 2013). Without creating new efficiency-based subsidy programs, we will need every farm and every farmer in Illinois actively implementing some form of end-of-pipe remediation practice to address this issue on such a scale.…”
Section: Biophysical and Social Science Results Inform Policy Decisionsmentioning
confidence: 99%
“…Research on the role of attitudes in decisions to adopt agricultural conservation practices have found positive associations between awareness of environmental problems, attitudes toward potential solutions, and willingness to adopt those solutions (Prokopy et al 2008). Strong positive attitudes toward pro-environmental behavior (Reimer et al 2011) and the relative importance of production and stewardship values to farmer identities (Burton 2004;McGuire et al 2012) have also been found to be important predictors of farmer conservation behavior. Research has shown that some farmers place more value on the outputs of agricultural production (e.g., yield and profit), while others tend to place more emphasis on conservation (Burton 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This shift does not require a change in farmer/rancher identity from "productivist" to "conservationist". Rather, it facilitates a more explicit focus on land management goals, and a broadening of what producers view as a "good" farmer/rancher that includes more conservation related goals [144]. Underlying this shift are two strategies for change.…”
Section: Governance Scale Shift: Farming Is Not Only Agricultural Promentioning
confidence: 99%